Strategi Komunikasi Pemasaran Film KKN Di Desa Penari Melalui Media Sosial - Faris Saputra Dewa (Lembaga Pengembangan Kinerja Dosen, 2022)
KKN di Desa Penari is a horror movie produced by MD Pictures. This Indonesian and Javanese language film managed to become the film with the highest number of cinemagoers in the history of Indonesian cinema with 9,233,847 viewers, replacing the film Warkop DKI Reborn: Jangkrik Boss! (Part 1) which released in 2016 with 6,858,616 viewers. Using a qualitative research method with a descriptive approach, this study aims to determine the marketing communication strategy for film KKN di Desa Penari through social media. The results of the study show that MD Pictures utilizes several social media such as YouTube, Instagram, Facebook, and Twitter in promoting film KKN di Desa Penari. Social media is used to provide accurate information about film showing schedules, cinemas showing films, and how to buy cinema tickets online. Creating interesting social media content such as countdown, giveaway event, collaborating with external parties in the form of discount promos, testimonials from mass media representatives, public figures, and cinema goers who have watched the film KKN di Desa Penari, and building interaction on social media through making funny pictures/memes via the @kknmovie account.